TEACHING GRAMMAR RULES IN PRACTICAL SPEECH - Almatova Nodira Anvar qizi,; Umirzaqova Iroda Yunus qizi,; Muhammadiyeva Mahliyo Ravshan qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
ANNOTATION The article examines methods of teaching English grammar rules in practical  speech.  It  highlights  the  importance of  applying grammar  in  real communicative  contexts  rather  than  just  learning  rules  theoretically.  The  study discusses  common  errors  made  by  students  in  speech,  their  causes,  and  effective strategies for correcting them. Pedagogical approaches such as role-plays, dialogues, interactive exercises, and error analysis are emphasized. The research demonstrates that  teaching  grammar  through  practical  speech  enhances  students’  communicative competence, encourages independent learning, and increases motivation.